Aeronautical applications of non-destructive testing - Fahr, Abbas (DEStech Publications Inc., 2014)
Provides a detailed assessment of non-destructive testing methods for the many materials and thousands of parts in aircraft. This book describes a wide variety of NDT techniques and explains their application in the evaluation and inspection of aerospace materials and components ranging from the entire airframe to systems and subsystems.